Development of Learning Media in Subjects Introduction to Computers: Pengembangan Media Pembelajaran Pada Matakuliah Pengantar Komputer - tri monarita johan; Febriyanno Suryana; Jeprimansyah jeprimansyah; Raimon Efendi (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2022)
Education has a role to improve the quality of its Human Resources (HR). The purpose of this research is to develop interactive multimedia-based learning media in the Introduction to Computer course. The method used in this development is the Research and Development (R&D) method. Research and development methods are methods used to produce certain products, and test the effectiveness of these products. The research and development itself is carried out based on an industry-based development model, the findings of which are used to design products and procedures, which are then systematically carried out by field tests, evaluated, refined to meet certain criteria for effectiveness, quality and standards. Interactive multimedia-based learning media in the Introduction to Computer course is proven to be able to increase conceptual understanding in Level III students. This can be seen from the results of the average student understanding of the pre-test control group 62.31 and the experimental group 69.81. From several validation experts, it means that this learning media does not need to be revised. However, this learning tool will still be improved based on suggestions and comments from each validation subject.